2015
DOI: 10.1002/jat.3126
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of uranium in the renal proximal tubules during acute renal uranium toxicity

Abstract: Renal toxicity is a hallmark of uranium exposure, with uranium accumulating specifically in the S3 segment of the proximal tubules causing tubular damage. As the distribution, concentration and dynamics of accumulated uranium at the cellular level is not well understood, here, we report on high-resolution quantitative in situ measurements by high-energy synchrotron radiation X-ray fluorescence analysis in renal sections from a rat model of uranium-induced acute renal toxicity. One day after subcutaneous admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…In addition, we have previously shown from in vivo experiments i using SIMS microscopy that uranium is heterogeneously distributed in the nephron and localized mainly in cell nuclei of proximal convoluted tubules (Poisson et al, ; Tessier et al, ). Similar uranium distribution has been observed using different imaging technic in case of acute renal contamination in rats (Homma‐Takeda et al, ). The lower resolution of particle induced X‐ray emission (PIXE) images in this study, compared to the SIMS microscopy did not allowed observing n heterogeneous subcellular distribution of uranium.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, we have previously shown from in vivo experiments i using SIMS microscopy that uranium is heterogeneously distributed in the nephron and localized mainly in cell nuclei of proximal convoluted tubules (Poisson et al, ; Tessier et al, ). Similar uranium distribution has been observed using different imaging technic in case of acute renal contamination in rats (Homma‐Takeda et al, ). The lower resolution of particle induced X‐ray emission (PIXE) images in this study, compared to the SIMS microscopy did not allowed observing n heterogeneous subcellular distribution of uranium.…”
Section: Discussionsupporting
confidence: 78%
“…It has been previously shown by us and others that at level below 1 µg/g of kidney for in vivo experiments and below 100 µM for in vitro experiments, close to realistic exposure levels, uranium did not induced direct deleterious toxic effects but induced biological pathways related to cell and tissue defense (Guéguen et al, ; Leggett et al, 1989; Prat et al, ). Recent in vivo experimental studies have confirmed that uranium distribution is highly heterogeneous within the kidney and can reach concentration tenfold higher than the mean renal tissue level (Homma‐Takeda et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…The precise location and accurate quantification of uranium in rodents' kidneys would facilitate trustworthy information for reconstructing a more realistic dosimetry model for a better estimation of health risk that could be related to renal dysfunction or cancer occurrence in workers exposed to uranium. To date, few quantitative studies have been carried out employing high-energy synchrotron radiation X-ray fluorescence (SR-XRF) analysis and X-ray absorption fine structure (XAFS) [16,17]. Unfortunately, the limited access to these analytical techniques limits considerably its daily use for routine analysis [18].…”
Section: Introductionmentioning
confidence: 99%
“…DU is a heavy metal and can emit α and β particles; thus, it exhibits both heavy metal toxicity and radiotoxicity. The kidney is the major target organ of acute DU exposure, and DU can cause severe necrosis of renal proximal tubule endothelial cells, ultimately leading to acute renal failure or even death345. The following mechanisms of action underlie the nephrotoxicity of DU6: (1) altering ion transport in cells to inhibit the oxidative phosphorylation of mitochondria and utilization of adenosine triphosphate (ATP); (2) altering the expression of certain genes (associated with inflammation, oxidative stress, and homeostasis); and (3) increasing oxidative stress levels and decreasing anti-oxidation in cells, thus increasing DNA damage and promoting apoptosis.…”
mentioning
confidence: 99%